Irrigation water quality in a framework of sustainable development goal 6: a review of challenges impacts policy alignments - Vranešević, Milica; Meseldžija, Maja; Grabić, Jasna; Zemunac, Radoš; Boukalova, Zuzana (Frontiers in Agronomy, 2025)
This review article aims to consolidate existing classification systems and evaluate the suitability of irrigation water in the context of Sustainable Development Goal 6 (SDG 6), with particular focus on targets 6.3, 6.4, and 6.5. The review explores key physico-chemical parameters of irrigation water quality and their role in determining water usability. Common classification systems such as FAO and US Salinity Laboratory (USSL) frameworks are examined, alongside their application in assessing impacts on soil health, crop productivity, and ecosystem stability. Findings indicate that inadequate irrigation water quality, particularly due to high salinity and sodium content, leads to soil salinization, reduced yields, and degradation of water and soil resources. These effects also extend to environmental and economic systems, through biodiversity loss and increased production costs. Effective management practices, such as improving drainage, using appropriate irrigation water, and applying soil amendments, are useful to mitigate these adverse effects and maintain soil and plant health. Mitigation strategies to address the economic impacts of unsuitable irrigation water quality include infrastructure investment, educational initiatives and policy enforcement. These strategies are closely aligned with European policy initiatives such as the Water Framework Directive, the European Green Deal, and the Blue Deal, all of which aim to promote sustainable irrigation practices and support the successful implementation of SDG 6 targets. The review emphasizes the practical relevance of these findings for policy-makers, water managers, and agricultural stakeholders seeking to implement sustainable irrigation practices and enhance local water resilience under SDG 6 targets.